A Comparative Cross-sectional Study on Prevalence of Low Birth Weight and its Anticipated Risk Factors - Assmaa A. Alsamae Bsc; Hala A. Elzilal PhD; Eman Alzahrani PhD; Hala M. Abo-Dief PhD; Mujeeb A. Sultan PhD (SAGE Publishing, 2023)
Objective. This study aims to highlight the low birth weight (LBW) in Taiz City (Yemen), as LBW is one of the public health challenges experiencing a profound effect on newborns. Methods. This was a cross-sectional study since the interview and medical records were the sources of data to be analyzed by SPSS. Results. The findings of this study include; a high prevalence of LBW (39.11%), the maternal age was not associated with LBW ( P  = .68), and education level, economic status, residence place, and health status were not associated with LBW ( P  < .05). Although the pre-pregnancy BMI, during-pregnancy BMI, MUAC, and gestational age were significantly associated with LBW ( P  < .05), the only risk factor was gestational age (OR = 9.606, CI = 3.988-23.135, P  = .00). Conclusion. LBW is highly prevalent in Taiz (Yemen), so providing good healthcare services is essential to manage LBW incidence.